Analisis Kualitas Air Dan Strategi Pengendalian Pencemaran Air Di Sungai Pepe Bagian Hilir, Surakarta - Ulfi Hanum; Muhammad Fadhil Ramadhan; Muhammad Fadhillah Armando; Muchammad Sholiqin; Siti Rachmawati (DPPM Universitas Pelita Bangsa, 2022)
River water quality is influenced by the natural conditions of the river, human activities and land use in the vicinity. Water pollution is the inclusion or entry of various kinds of objects, living things, energy, substances and other components into the air by human activities, which then causes air quality to decrease to a certain level so that it cannot be utilized according to its use. Pepe River is one of the rivers that pass through the Surakarta area. Pepe River is divided into two, namely Pepe Hulu and Pepe Hilir. The Pepe Hilir River is 5.76 km long. Pollution that occurs in the Pepe River is dominated by household waste. The water quality of the Pepe Hilir River is classified as class IV. This study aims to determine the pollution of the Pepe Hilir River so that it can provide recommendations for water management strategies for the Pepe Hilir River. This study uses descriptive quantitative methods obtained through observation and journal literature related to physico-chemical parameters in river water. The results showed that the level of water pollution of the Pepe Hilir River was said to be good at the three research locations, not showing any water pollution based on the results of measurements using HORIBA U-50 (Multiparameter Water Quality Checker). Based on secondary data in the form of previous research, it shows that the Surakarta City government has promoted the Pepe River pollution control strategy, but community participation is still considered minimal. Therefore, the recommendation for the government is that the government prioritizes the community so that they are able to contribute to waste management on the banks of the Pepe River with outreach campaigns to villages traversed by the Pepe Hilir River. The government can also understand with community leaders or community institutions to help encourage the community to want to participate in river management programs. In addition, the Surakarta city government is also advised to provide great opportunities for the community to be involved in programs promoted by the government. Keywords: Water Quality, Water Pollution, River